2016
DOI: 10.1007/7854_2016_53
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacology of 3,4-Methylenedioxypyrovalerone (MDPV), Its Metabolites, and Related Analogs

Abstract: 3,4-Methylenedioxypyrovalerone (MDPV) is a psychoactive component of so-called bath salts products that has caused serious medical consequences in humans. In this chapter, we review the neuropharmacology of MDPV and related analogs, and supplement the discussion with new results from our preclinical experiments. MDPV acts as a potent uptake inhibitor at plasma membrane transporters for dopamine (DAT) and norepinephrine (NET) in nervous tissue. The MDPV formulation in bath salts is a racemic mixture, and the S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 107 publications
(156 reference statements)
2
66
0
Order By: Relevance
“…They are non-substrate transporter inhibitors, showing inhibitory potencies at NE transporter and DAT methylamphetamine 13 or cocaine. 14,15 MDPV and α-PVP are both considered to be cocaine-like, whilst being more effective reinforcers. 16 Recent research on the pyrovalerone analogue α-pyrrolidinopentiothiophenone (α-PVT) suggests it has reinforcing and rewarding effects similar to those of both methylamphetamine and cocaine.…”
Section: Clinical Neuropharmacological Issuesmentioning
confidence: 99%
See 3 more Smart Citations
“…They are non-substrate transporter inhibitors, showing inhibitory potencies at NE transporter and DAT methylamphetamine 13 or cocaine. 14,15 MDPV and α-PVP are both considered to be cocaine-like, whilst being more effective reinforcers. 16 Recent research on the pyrovalerone analogue α-pyrrolidinopentiothiophenone (α-PVT) suggests it has reinforcing and rewarding effects similar to those of both methylamphetamine and cocaine.…”
Section: Clinical Neuropharmacological Issuesmentioning
confidence: 99%
“…17 It has been suggested that the reinforcing properties of cathinone stimulants are positively correlated with their selectivity for the dopamine (DAT) relative to SERT. 15,[18][19][20] What is already known about this subject • NPSfinder ® has identified some 41 cathinone molecules not known to either the UNODC or EMCDDA.…”
Section: Clinical Neuropharmacological Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of studies have shown that the stimulation of synthetic cathinones is closely related to changes in neurotransmitters such as dopamine (DA) serotonin (5‐HT) and their metabolites 3,4‐dihydroxyphenylacetic acid (DOPAC), 3‐methoxytyramine (3‐MT) and 5‐hydroxyindole‐3‐acetic acid (5‐HIAA) in the brain (Baumann et al, ; Baumann et al, ; Baumann, Partilla, & Lehner, ; De Felice, Glennon, & Negus, ; Lopez‐Arnau et al, ; Lopez‐Arnau, Martinez‐Clemente, Pubill, Escubedo, & Camarasa, ; Martinez‐Clemente, Escubedo, Pubill, & Camarasa, ; Marusich, Gay, & Blough, ; Simmler et al, ). Therefore, studying the changes in NEP, DA, 5‐HT, DOPAC, 3‐MT and 5‐HIAA concentration will help us understand the effects of NEP on dopaminergic and serotonergic systems.…”
Section: Introductionmentioning
confidence: 99%